PENDIDIKAN KARAKTER DALAM MAKNA SIMBOLIK TOPENG LENGGER WONOSOBO - Ari Eko Budiyanto (Journal of Social Sustainability Management, 2022)
Character is a distinctive personality in a person who is formed due to the influence of his environment. Traditional arts in each region have important meanings and functions for the community. Apart from being a spectacle or entertainment, folk art also functions as a medium of education. Lengger mask art contains ethical and aesthetic teachings in the form of visual appearances and living symbolism which can basically lead humans to perfection and true identity. The interesting thing about the lengger mask is from its presentation, namely from the presentation of motion, accompaniment or music in this case is cute or poetry, clothing and masks that contain character education values ​​that can be used as learning for the surrounding community and actors. the art. Learning in this case is an effort to build character that is applied to oneself and society. The symbolic meaning of the lengger mask is found in the shape of the eyes, nose, mouth, color, and symbols on the mask ornament. The lengger Giyanti Wonosobo mask, apart from being an entertainment or spectacle, also teaches about the values ​​contained in accordance with local wisdom so that it can make learning for the wider community and traditional arts actors. The character education values ​​contained in the lengger mask art can be classified as character education values ​​in relation to God, oneself, others, and nationality.